2019
DOI: 10.1186/s12891-019-2729-3
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin inhibits patellar tendon healing in rats: a histological and biochemical evaluation

Abstract: Background Female patients are more likely to have tendon injuries than males, especially those who has a higher concentration of relaxin. Previous studies have demonstrated that relaxin attenuates extracellular matrix (ECM) formation. However, the mechanism of relaxin on tendon repair remains unclear. We hypothesize that relaxin inhibits tendon healing by disrupting collagen synthesis. Methods A patellar tendon window defect model was established using Sprague-Dawley r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…RLX also reduces the degree of scar formation[ 18 ]. Unemori et al [ 19 ] and Mookerjee et al [ 20 ] found that RLX inhibited the differentiation of renal fibroblasts and collagen deposition by inhibiting phosphorylation of Smad2, thus interfering with TGF-β1[ 21 , 22 ]. An increase in RLX levels also causes ligament and tendon injury.…”
Section: Discussionmentioning
confidence: 99%
“…RLX also reduces the degree of scar formation[ 18 ]. Unemori et al [ 19 ] and Mookerjee et al [ 20 ] found that RLX inhibited the differentiation of renal fibroblasts and collagen deposition by inhibiting phosphorylation of Smad2, thus interfering with TGF-β1[ 21 , 22 ]. An increase in RLX levels also causes ligament and tendon injury.…”
Section: Discussionmentioning
confidence: 99%
“…With the aging of the population and the increase in physical activity, the incidence of tendon injury has increased significantly. According to conservative reports, more than 30 million tendon injuries occur worldwide each year, [ 4 ] which represent a serious societal problem that must be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Within the orthopaedic field, tendinopathy is one of the most frequently self reported musculoskeletal injuries in the athletic and working populations, which result in pain, swelling and impaired function [ 2 ]. More than 30 million tendon injuries are reported annually worldwide, while the actual number might be even higher since many injuries are not reported [ 3 ]. The elderly population and athletes are predominantly affected by tendon injuries.…”
Section: Introductionmentioning
confidence: 99%